Role of direct immunofluorescence on outer root sheath of hair follicle in monitoring disease activity of pemphigus vulgaris (Journal of Pathology of Nepal, 2017)
Background:   Since the outer root sheath of hair follicle is structurally analogous to epidermal keratinocytes, direct immunofluorescence of hair may be an alternate method for monitoring disease activity of pemphigus vulgaris. Our objective was to find the effectiveness of direct immunofluorescence of outer root sheath as an alternate method in monitoring patients with pemphigus vulgaris.  Materials and methods: Sixteen diagnosed cases of pemphigus vulgaris and in clinical remission for at least three months were enrolled. Skin biopsy sample and five plucked scalp hair samples of each patient were stained with Fluorescein isothiocyanate conjugate .Results: Hair direct immunofluorescence was positive in 13 (81.25%) patients and skin direct immunofluorescence was also positive in 13 patients (81.25%).Conclusion: Direct immunofluorescence of hair is a simple, specific and non-invasive method, and provides the opportunity to avoid repeated skin biopsies as an appropriate alternative technique for the disease monitoring in patients with pemphigus vulgaris.